PELAKSANAAN PERATURAN DAERAH PROVINSI RIAU NOMOR 18 TAHUN 2013 TENTANG PERLINDUNGAN DAN PEMBERDAYAAN DISABILITAS (STUDI MENGENAI AKSESIBILITAS PENYANDANG DISABILITAS DI PUSKESMAS REJOSARI KOTA PEKANBARU TAHUN 2019) - Holis Saputra; Wan Asrida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Policy implementation is one of the most important things in running the government. If the policies that have been made are not implemented properly, it will not have any impact on the target community. Regional Regulation Number 18 of 2013 concerning the Protection and Empowerment of Persons with Disabilities, this regulation regulates the provision of accessibility for persons with disabilities in Puskesmas. The purpose of this study was to observe the implementation of the Regional Regulation No. 18 of 2013 regarding the Accessibility of Persons with Disabilities at the Rejosari Health Center, Pekanbaru City.This study uses the theory of George Edwards, according to Edwards there are four factors that influence policy implementation, namely, communication, resources, disposition and bureaucratic structure. The research approach used is qualitative with descriptive analysis method by describing phenomena and data accurately. The research location is at the Rejosari Health Center, Pekanbaru City. The types of research data are primary data and secondary data. Data collection techniques used by interview and documentation.The result of this study is to look at the factors that influence the implementation of Regional Regulation No. 18 of 2013 regarding the accessibility of persons with disabilities at the Rejosari Health Center Pekanbaru City. In implementing the policies of the Pekanbaru City Health Office and Pekanbaru City Health Center Rejosari, there is still a lack of socialization of Regional Regulation No. 18 of 2013, so that the essence of the importance of providing accessibility for persons with disabilities at Rejosari Health Center Pekanbaru City has not been conveyed. The Pekanbaru City Rejosari Health Center has not prioritized providing accessibility for people with disabilities at the Puskesmas and there is still a lack of coordination between the Pekanbaru City Health Office, the Pekanbaru City Rejosari Health Center, and parties with disabilities to provide accessibility at the Pekanbaru City Health Center.Keywords: Policy Implementation, Provision of Accessibility in Puskesmas